PENGARUH MODEL MAKE A MATCH BERBANTUAN LKS TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROKARBON - lestari, Puji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractBackground of this research is students learning outcomes is low, so this research aims to determine: (1) the difference in learning outcomes between students who were taught using Make A Match model assisted with work sheets with the students taught by using conventional model, (2) the magnitude of the effect of Make A Match model assisted with work sheets in X grade students of SMA Santo Fransiskus Asisi Pontianak. The research method was Quasi Experimental Design with Nonequivalent Control Group Design. Samples were taken by means of purpossive sampling. Instruments in this research were Â Â learning outcomes test and interview guidelines. Based on data analysis with U-Mann Whitney test, Î±=5%, the result shows that the probability is around 0, 008<0, 05. The result of data analysis showed that there was difference in learning outcomes between students who were taught using Make A Match model assisted with work sheets with students who were taught using the conventional model. Make A Match assisted with work sheets give influenced by 30,51 % towards the increasing in students learning outcomes in hydrocarbon solutions material at SMA Santo Fransiskus Asisi Pontianak. Keywords: Make a Match, work sheets, hydrocarbon, learning outcomes.Â